Intrapartum ultrasound to predict vaginal labor: a prospective cohort study - Ingeberg, Helene; Miskova, Anna; Andzane, Diana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Non-invasive transperineal ultrasound has been used to detect the descent of the fetal head using head-perineum distance (HPD) and angle of progression (AOP). The aim was to evaluate HPD and AOP as predictors of vaginal delivery in the first stage of labor. Methods: This was a prospective cohort study in Riga Maternity Hospital in Latvia from May till August 2016. The study included only nulliparous women with singleton pregnancies and cephalic presentation. Ultrasound was used to measure HPD and AOP. Data was collected on demographics, labor parameters and outcome. Results: Of 36 women enrolled, 26 (72.2%) had a vaginal delivery. The area under the receiver–operating characteristics curve for the prediction of vaginal delivery was 0.865 (95% confidence interval (CI) 0.75-0.98) using HPD as the test variable and the area under the curve was 0.877 (95% CI 0.77-0.99) for AOP. The median HPD was lower in the women delivering vaginally than in the women delivering by cesarean section (P<0.001). HPD was ≤40 mm in 18 (50%) women, of whom all delivered vaginally. HPD was >40 mm in the other 18 women, of whom 8 (22.2%) delivered vaginally (P<0.001). AOP was ≥105° in 22 (61.1%) women and, of these, 21 delivered vaginally. AOP was <105° in the other 14 (38.9%) women, of whom 5 delivered vaginally (P<0.001). Conclusions: HPD ≤40 mm and AOP ≥105° are both predictive of vaginal delivery in the first stage of labor.